Studi Medan Elektromagnetik pada Pembangkit Listrik Tenaga Surya - Yuninda Triyatne; Ardian Nurarifin; Sonata Mahardika; Umar Hamzah; Diyajeng Luluk Karlina (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research investigates the electromagnetic field (EMF) characteristics generated by solar power plants, focusing on their potential environmental and health impacts. The study employs a dual methodology combining direct measurements using gaussmeters and computer simulations using COMSOL software to map electromagnetic fields around solar power installation components. Measurements were taken under two conditions: during solar power plant operation and non-operation, to establish comparative baseline data. The research found significant variations in electromagnetic field intensity based on operational status and distance from components, particularly near inverters and cable networks. Results indicate that EMF levels are higher during operation, with field strength decreasing exponentially with distance from the source. These findings contribute to understanding EMF distribution patterns in solar installations and provide valuable insights for implementing appropriate mitigation strategies to ensure safe operation within established exposure standards.